Synergetic adsorption and photocatalytic degradation of pollutants over 3D TiO2–graphene aerogel composites synthesized via a facile one-pot route. Issue 8 (15th July 2016) - Zhang, Jing-Jie; Wu, Yu-Hui; Mei, Jin-Ya; Zheng, Guang-Ping; Yan, Ting-Ting; Zheng, Xiu-Cheng; Liu, Pu; Guan, Xin-Xin
Abstract : A series of 3D TiO2 –GA composites were successfully self-assembled, which exhibited excellent adsorption capacities and visible light photocatalytic activity in the degradation of RhB. Abstract : A series of composites consisting of anatase TiO2 nanocrystals and three-dimensional (3D) graphene aerogel (TiO2 –GA) were self-assembled directly from tetrabutyl titanate and graphene oxides via a one-pot hydrothermal process. TiO2 was found to uniformly distribute inside the 3D network of GA in the resulting composites with large surface areas ( S BET > 125 m 2 g −1 ) and high pore volumes ( V p > 0.22 cm 3 g −1 ). In comparison with GA and TiO2, the composites possessed much higher adsorption capacities and visible light photocatalytic activity in the degradation of rhodamine B (RhB). With an initial concentration of 20.0 mg L −1 of RhB, the adsorptive decolourization of RhB was as high as 95.1% and the total decolourization value reached up to 98.7% under visible light irradiation over 5.0 mg of the resulting composites. It was elucidated that the physical and chemical properties of the TiO2 –GA composites could be ascribed to their unique 3D nanoporous structure with high surface areas and the synergetic activities of graphene nanosheets and TiO2 nanoparticles.